ANALISIS DAMPAK REFORMASI PAJAK 2009 TERHADAP KINERJA PAJAK DI INDONESIA (KHUSUS PPN DAN PPNBM) - MARTHA SARI, LYA Martha (Jurnal Akuntansi AKUNESA, 2013)
Taxes constitutes to sectorally essential that becomes to prioritise government as sourceof States main acceptance. Utilised optimize State taxes acceptance, ditjen is Taxes doesreform on Statute VAT & Sales Taxon Luxurious Goods. To the effect of observational itis know impact marks sense taxes reform on VAT & Sales Taxon Luxurious Goods Lawto state taxes acceptance. After marks sense changing deep VAT and Sales TaxonLuxurious Goods Law apparently accepting state of that taxes type haven't reachedrealization target. It because of marks sense taxes restitution that is begat marks sensetaxation legislation regulation that let taxpayer for can delay taxes payment liabilitiesits upon propose objection and appeal. Therefore, tax sistem at our state stills to have isfixed to reach state acceptance target for further year.Keywords : Taxes reform, income tax, restitution.